Efficient generation of monoclonal antibodies against peptide in the context of MHCII using magnetic enrichment - Justin A. Spanier (Nature Portfolio, 2016)
Generating antibodies specific for the peptide–MHCII complexes has been challenging, with only a handful made to date. Here, the authors develop a more efficient approach to generate these antibodies, and demonstrate their potential in research and therapeutic applications.